1995
DOI: 10.2172/130675
|View full text |Cite
|
Sign up to set email alerts
|

CHEMCON User`s Manual, Version 3.1

Abstract: Portions of this document may be illegible in electronic image products. Images are produced from the best available original document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…If surface temperatures are low enough, mobilization of hazardous material is minimized. The CHEMCON code [36] Fig. 42.…”
Section: Loca Calculationsmentioning
confidence: 99%
“…If surface temperatures are low enough, mobilization of hazardous material is minimized. The CHEMCON code [36] Fig. 42.…”
Section: Loca Calculationsmentioning
confidence: 99%
“…The heat transfer code CHEMCON [10] has been used to simulate a LOFA and to assess the dissipation of afterheat during the transient. It has been found that the decay heat rapidly transfers through radiation to the cooler structures (shielding and confinement building).…”
Section: Loss-of-flow Accident Analysismentioning
confidence: 99%
“…These data have been used with the heat transfer capability of the CHEMCON code 18 to obtain radioactivity source terms during accident scenarios in both IFE and MFE. CHEMCON was developed by the INEEL FSP to analyze thermal transients and has been updated to account for new experimental data and a more realistic oxidation package.…”
Section: Safety Assessment Tool Developmentmentioning
confidence: 99%